Nutritional/Chemical Constituents and Free Radical Scavenging Potentials of the Aqueous Extract of Phoenix dactylifera Fruit - Oyegoke Rukayat Abiodun (Khalij-Libya Journal of Dental and Medical Research, 2024)
Aims: Phoenix dactylifera fruit, grown majorly in northern part of Nigeria is acclaimed to possess numerous nutritional and medicinal properties. The study was carried out to investigate the nutritional/chemical constituents and the free radical scavenging potentials of the aqueous extract of Phoenix dactylifera fruit. Methods: The aqueous extract of the fruit was subjected to standard analytical test to assay for the amino acids, phytochemicals and free radical scavenging potentials: Phytochemicals and amino acids screening was carried out via High Performance Liquid Chromatography and Gas Chromatography Mass Spectrometry analyses. The antioxidant effects of the extract on free radicals were determined on radicals 2,2'-azino-bis (3-ethylbenzothiazoline-6-sulfonic acid) , 2, 2-diphenyl-1-picrylhydrazyl , Nitric oxide and Hydroxyl radical. Results: Results revealed the presence of seven secondary metabolites with a high steroid and flavonoid content and low Coumarins, Glycosides, Alkaloids, Saponin, and Terpenoid concentration. The HPLC analysis of the phytochemical showed that it contained fifteen phytocompounds, seventeen amino acids while GCMS analysis reveals eleven fatty acids. For the free radical scavenging activity, it was able to inhibit ABTS, DPPH, NO, and OH-, in a concentration dependent manner. Conclusions: The results indicate that the fruit possess good nutritional properties and abundant secondary plant metabolites constituents and this might provide evidence which corroborates with the free radical scavenging potentials of the fruit. الأهداف: من المعروف أن فاكهة فونيكس، التي تنمو بشكل رئيسي في الجزء الشمالي من نيجيريا، تمتلك العديد من الخصائص الغذائية والطبية. أجريت هذه الدراسة لمعرفة المكونات الغذائية والكيميائية وإمكانات التخلص من الجذور الحرة للمستخلص المائي لفاكهة Phoenix dactylifera. الطرق: تم إخضاع المستخلص المائي للثمرة لاختبار تحليلي قياسي لفحص الأحماض الأمينية والمواد الكيميائية النباتية وإمكانات تنظيف الجذور الحرة: تم إجراء فحص المواد الكيميائية النباتية والأحماض الأمينية عن طريق تحليل كروماتوغرافيا سائلة عالية الأداء وتحليلات مطياف الكتلة كروماتوغرافيا الغاز. تم تحديد التأثيرات المضادة للأكسدة للمستخلص على الجذور الحرة على الجذور 2،2'-أزينو-مكرر (3-إيثيل بنزوثيازولين-6-حمض السلفونيك)، 2، 2-ثنائي فينيل-1-بيكريل هيدرازيل، وأكسيد النيتريك وجذر الهيدروكسيل. النتائج: أظهرت النتائج وجود سبعة مستقلبات ثانوية ذات محتوى عالي من الستيرويد والفلافونويد وانخفاض تركيز الكومارينات والجليكوسيدات والقلويدات والسابونين والتيربينويد. أظهر تحليل HPLC للمادة الكيميائية النباتية أنها تحتوي على خمسة عشر مركبًا نباتيًا وسبعة عشر حمضًا أمينيًا بينما أظهر تحليل GCMS أحد عشر حمضًا دهنيًا. بالنسبة لنشاط مسح الجذور الحرة، كان قادرًا على تثبيط ABTS، DPPH، NO، وOH-، بطريقة تعتمد على التركيز. الاستنتاجات: تشير النتائج إلى أن الثمرة تمتلك خصائص غذائية جيدة ومكونات أيضية نباتية ثانوية وفيرة، وهذا قد يوفر دليلاً يدعم إمكانات الفاكهة في التخلص من الجذور الحرة.